Evolutionary and Functional Analysis of Membrane-Bound NAC Transcription Factor Genes in Soybean. Issue 3 (26th September 2016) - Li, Shuo; Wang, Nan; Ji, Dandan; Xue, Zheyong; Yu, Yanchong; Jiang, Yupei; Liu, Jinglin; Liu, Zhenhua; Xiang, Fengning
Abstract : Multiple levels of functional divergence contributed to gene retention after whole-genome duplication in the soybean membrane-bound NAC transcription factors gene family. Abstract: Functional divergence is thought to be an important evolutionary driving force for the retention of duplicate genes. We reconstructed the evolutionary history of soybean ( Glycine max ) membrane-bound NAC transcription factor (NTL) genes. NTLs are thought to be components of stress signaling and unique in their requirement for proteolytic cleavage to free them from the membrane. Most of the 15 GmNTL genes appear to have evolved under strong purifying selection. By analyzing the phylogenetic tree and gene synteny, we identified seven duplicate gene pairs generated by the latest whole-genome duplication. The members of each pair were shown to have variously diverged at the transcriptional (organ specificity and responsiveness to stress), posttranscriptional (alternative splicing), and protein (proteolysis-mediated membrane release and transactivation activity) levels. The dormant (full-length protein) and active (protein without a transmembrane motif) forms of one pair of duplicated gene products (GmNTL1/GmNLT11) were each separately constitutively expressed in Arabidopsis ( Arabidopsis thaliana ). The heteroexpression of active but not dormant forms of these proteins caused improved tolerance to abiotic stresses, suggesting that membrane release was required for their functionality. Arabidopsis carrying the dormant form of GmNTL1 was more tolerant to hydrogen peroxide, which induces its membrane release. Tolerance was not increased in the line carrying dormant GmNTL11, which was not released by hydrogen peroxide treatment. Thus, NTL-release pattern changes may cause phenotypic divergence. It was concluded that a variety of functional divergences contributed to the retention of these GmNTL duplicates.